Artificialização do sedimento fluvial em corpos hídricos da bacia do córrego da Água Branca – Itirapina/SP - Toyama, Daniele (2020)
The human being, as a modifying agent of the physical environment, causes environmental degradation and the aquatic compartment, including streambed sediments, has a high capacity to accumulate and absorb traces of these changes. Understanding the uses of the hydrographic basin is an important environmental management tool given that the type and intensity of the degradation suffered varies according to the type and intensity of land use. In the present work, an investigation was carried out on the occurrence of the artificialization of river deposits and quantification of this phenomenon considering a core sample of the sediment. For this purpose, collections of core samples were carried out in the rainy and dry season, in locations that covered a variety of uses, and the land use was mapped. For the analysis of the sediment, granulometric separation, degradation of organic matter, visual analysis with a magnifying glass of the thicker material, and analysis of medium granulometry material with a stereomicroscope were performed. Additionally, the finer material was analyzed with a scanning electron microscope, and chemical mapping by dispersive energy spectroscopy and thermogravimetry and differential exploratory calorimetry tests were conducted in order to detect the presence of plastics. It was observed that sedimentation of artificial material occurs in the bed of streams in the study area (macroplastics, construction waste, rubber and cardboard). The most abundant materials incorporated into the sediment profile are microplastics (fragments and fibers). In the thinnest portion of the sediment, anthropogenic microparticles were observed and the presence of some types of plastic (nylon, LDPE and PET) was detected. Areas of more intense urban occupation and with less riparian vegetation suffer more from this degradation and areas of rural use, less. The existing dam in the basin accumulates more materials (both macro and microplastics), also playing the role of preventing these residues from being transported downstream of the water body. The importance of investing in environmental management measures is highlighted, such as environmental education, restoration of riparian vegetation, inspection of environmental legislation, and public cleaning to settle the impacts that poor management of solid waste causes in the aquatic environment.